Resisting stigma, embracing solidarity: An ethnographic study of shopaholics anonymous - Rachel Demerling (Qualitative Studies, 2011)
In recent years, an increased interest in the phenomenon of compulsive buying, which is better known as “shopaholism”, has occurred. This behaviour has been conceptualized as being an uncontrollable urge to purchase things which is pleasurable for an individual or relieves their distress and which results in negative consequences for that individual. This article examines the experiences of individuals within a Shopaholics Anonymous group to understand why individuals decide to join a support group and explore the dynamics of interaction among participants and how that shapes the outcome of their addiction.